Dor, função motora e psicoemocional de pacientes com lombalgia crônica inespecífica - Leite, Paula Michele dos Santos (2016)
Low back pain is a common, debilitating and disabling condition, and the second leading cause of pain in approximately 70-85% of individuals at some point in life. Although 90% of acute low back pain cases are resolved within six weeks, about 7% of individuals develop chronic low back pain, which affects many aspects of your life as sensory, functional, psycho-emotional and quality of life. Supposedly the greater the pain, the greater the deficit in these respects, however, this relationship is not well established. Thus, the objectives of this study were to compare the sensory factors, functional, psycho-emotional and quality of life in patients with non-radicular low back pain over the magnitude of the pain; analyze, in detail, the nociceptive aspects and characteristics of pain in these subjects; evaluate the functionality of individuals; observe the psycho-emotional profile of these patients; investigate the quality of life of the subject. In this cross-sectional study patients with non-radicular low back pain, which had at least 12 weeks of low back pain. After evaluation, the subjects were divided into three study groups, according to the magnitude of his reported pain in Numerical Pain Scale (0-10). The groups were pain Mild, Moderate and Severe Pain Pain. Besides the Numerical Pain Scale, we used the questionnaire of McGill pain, algometry pressure, esthesiometry, temporal summation and conditioned pain modulation to investigate the nociceptive aspects. The functionality was assessed by muscle strength and flexibility, Oswestry Questionnaire Disability Index (ODI) and Roland Morris Disability Questionnaire (QIRM). To observe the psycho-emotional aspects were used to Catastrophizing Pain Scale (ECD), Tampa kinesiophobia Scale (ECT). Quality of life was investigated using EQ-5D Questionnaire. There was a statistically significant difference between groups in the Force variables (P = 0.004) and Oswestry (P = 0.001). The same could not be observed in other sensory and psycho-emotional variables, as well as quality of life. Functionality appears to be the main factor that appears differently with increasing level of pain of patients. Sensory and psycho-emotional aspects seem to influence the frame similarly patient, regardless of the pain intensity reported by him. The fact that the pain is chronic seems to be enough to trigger sensory and psycho-emotional changes of similar intensity, regardless of the level of pain.